1994
DOI: 10.1039/c39940002169
|View full text |Cite
|
Sign up to set email alerts
|

Addition of alkenes to tricarbonyl(vinylketene)iron(o) complexes and the synthesis of cyclopropanes

Abstract: The tricarbonyl(vinylketene)iron(o) complex 1 reacts with electron-poor alkenes to give decarbonylated adducts 3 and these are oxidised to tetrasubstituted cyclopropanes 4 using CAN; an X-ray crystal structure analysis of the adduct formed from 1 and dimethyl fumarate define its relative stereochemistry. But But3ad / 1 2a-d 4b-d a R1 = C02Me, R2 = H, R3 = C02Me; b R1 = H, R2 = C02Me, l? = C02Me; c R' = H, F? = COMe, R3 = C02Me; d R' = H, R2 = CF3, R3 = C02Et

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The ever-growing and longstanding interest in Fe(0) complexes stems mainly from their structural diversity and widespread applications. Nowadays, the utility of such compoundsmainly issued from conventional α,β-unsaturated systemsranges, inter alia, from potential new applications in organic synthetic chemistry to the usual efforts in understanding fundamental chemistry and physical properties. …”
Section: Introductionmentioning
confidence: 99%
“…The ever-growing and longstanding interest in Fe(0) complexes stems mainly from their structural diversity and widespread applications. Nowadays, the utility of such compoundsmainly issued from conventional α,β-unsaturated systemsranges, inter alia, from potential new applications in organic synthetic chemistry to the usual efforts in understanding fundamental chemistry and physical properties. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, tricarbonyliron(0) complexes of α,β-unsaturated ketones react with alkylithium reagents under an atmosphere of nitrogen to afford 1,4-diketones, while under an atmosphere of carbon monoxide, tricarbonyl(η 4 -vinylketene)iron(0) complexes are generated in good yield . Thomas and co-workers have used these iron(0)vinylketene complexes to synthesise a number of important organic products, including phenols, cyclopentadienones, cyclopropanes, β,γ-unsaturated carbonyl compounds, and vinylketeneimines …”
Section: Introductionmentioning
confidence: 99%
“…For instance, tricarbonyliron(0) complexes of R,β-unsaturated ketones react with alkylithium reagents under an atmosphere of nitrogen to afford 1,4-diketones, 5 while under an atmosphere of carbon monoxide, tricarbonyl(η 4 -vinylketene)iron(0) complexes are generated in good yield. 6 Thomas and co-workers have used these iron(0)vinylketene complexes to synthesise a number of important organic products, including phenols, cyclopentadienones, 7 cyclopropanes, 8 β,γ-unsaturated carbonyl compounds, 9 and vinylketeneimines. 10 Organometallics 1997, 16, 3221-3228 S0276-7333(97)00171-4 CCC: $14.00 © 1997 American Chemical Society In contrast, the reactivity of organolithium nucleophiles with binuclear complexes bearing σ-η-coordinated unsaturated hydrocarbyl ligands is relatively undeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…This process is well-known to occur with retention of stereochemistry and others have reported that the oxidative decomplexation of (pentenediyl)iron complexes bearing an electron-withdrawing substituent provides a novel methodology to generate vinylcyclopropanes . We herein report on an unexpected stereochemical outcome for certain substrates and propose a mechanism to account for these results.…”
mentioning
confidence: 99%